THE EFFECT OF FINANCIAL TECHNOLOGY ON THE PROFITABILITY OF BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Rindiani Rizfania Putri; Ardi Paminto; Jamaluddin (RADJA PUBLIKA, 2025)
This study is motivated by the rapid growth of Indonesia’s digital economy, marked by the emergence of financial technology (fintech) as a disruptive force in financial services. The research aims to analyze the influence of fintech, proxied by the number of ATMs, mobile banking transactions, and internet banking transactions, on bank profitability measured by Return on Assets (ROA) among banks listed on the Indonesia Stock Exchange during 2017–2023. Firm size and BOPO serve as control variables. A quantitative method with panel data regression was applied using EViews 13. The results show that the number of ATMs has a negative and significant effect on profitability, while mobile and internet banking transactions have positive and significant effects. Fintech enhances bank performance through cost efficiency, increased transaction volume, and non-interest income, with implications for future studies considering external factors.